A interdisciplinaridade no contexto das trilhas de aprofundamento do Novo Ensino Médio em Santa Catarina: das perspectivas e das limitações - Presotto, Keila Sabadin (2024)
This dissertation is linked to the line of research Educational Processes and Language, from Postgraduate Program in Education at the University of Passo Fundo-RS. The study seeks answer the following question: How was interdisciplinarity implemented in the Trilhas de Deepening the New Secondary Education (NEM) in Santa Catarina, considering the vision of Mathematics teachers? To this end, the objective was to understand the perspectives of interdisciplinary work in the Mathematics discipline in the NEM Deepening Tracks, in 2023, in state schools belonging to the Regional Education Coordination of Concordia-SC. The specific objectives consisted of: a) conceptualizing and understanding the interdisciplinarity, in light of the concepts of Hilton Japiassu (1976) and Ivani Fazenda (2006), considered precursors of the discussion on the topic in Brazil; b) understand how the interdisciplinarity is being considered in contemporary scientific work; w) identify the recommendations of official documents from Brazil and Santa Catarina on the interdisciplinarity; d) understand the organization of the NEM in state schools and whether the Deepening Tracks help in the context of interdisciplinary training. The search will it is based, above all, on the concepts of Japiassu (1976) and Fazenda (2006), in dissertatios contemporary studies on the subject and the legal frameworks that guide education in Brazil and the state from Santa Catarina. In this way, the following was developed: a) review of studies on the topic, in order to conceptualize and understand interdisciplinarity; b) research in official documents, to understand the legal aspects of the NEM; c) semi-structured interviews with eight school teachers Mathematicians who worked on the Deepening Tracks in 2023; using Analysis Discursive Textual (Moraes; Galliazzi, 2006). Based on semi-structured interviews with teachers, three categories of analysis were defined: (1) participants’ conception of the interdisciplinarity; (2) the view of Mathematics teachers on interdisciplinarity on the Deepening Trails; (3) the development of Deepening Trails. You results indicate that, although they are aware of the importance of interdisciplinarity, participants had difficulties implementing the Trails, such as the lack of collective planning, dialogue between teachers and support from the management team. Some teachers managed to develop interdisciplinary work, but in a one-off. It was concluded that, to work with Deepening Trails, it is necessary to have a truly interdisciplinary work and this is possible, as long as there is investment in training teacher, in the reorganization of the physical and pedagogical structures of schools, specific classes for planning and greater management support.